2000
DOI: 10.1111/j.1572-0241.2000.03371.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Previous Hbv Infection on The Course of Chronic Hepatitis C

Abstract: The prevalence of anti-HBc is high among HCV-positive individuals. HCV-positive individuals who are anti-HBc positive have: 1) a higher prevalence of cirrhosis; 2) lower HCV-RNA levels; and 3) an impaired ability to respond to interferon treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 30 publications
4
63
1
3
Order By: Relevance
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 59%
“…These results suggest that occult HBV infection may interfere with the clinical picture of chronic HCV infection, accelerating its evolution to cirrhosis (11). Evidence for previous HBV infection even in the absence of HBV DNA detection has been related to the severity of the disease in anti-HCV-positive chronic hepatitis patients (12) but these results were not confirmed by other investigators (13)(14)(15).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nosso achado vai contra a teoria da manutenção residual do vírus B neste cenário, sugerindo desta forma a ausência de seus epítopos em hepatócitos, ao menos em quantidades suficientemente capazes de induzir uma maior resposta citotóxica e fibrogênica, ou mesmo pautando a hipótese da supressão não citolítica de sua suposta replicação viral, exercido por células T através da liberação de citoquinas capazes de suprimir a transcrição de seu genoma sem causar dano celular 22 . Embora não realizada neste estudo, a diferenciação entre o padrão anti-HBcAg isolado e o perfil sorológico completo (anti-HBcAg[+] e anti-HBsAg[+]) para a avaliação da influência da infecção pregressa pelo VHB na hepatopatia do vírus C foi proposta por alguns autores, partindo do pressuposto de que a primeira situação estaria associada a um maior dano hepático 6,23 . Contudo, neste ponto a literatura tem demonstrado resultados conflitantes.…”
Section: Discussionunclassified
“…O curso da doença é dinâmico e altamente influenciado por uma gama de fatores exógenos e endógenos ao hospedeiro De fato, esta população apresenta marcadores de infecção pregressa pelo vírus B em maior frequência do que na população geral 4 . Estima-se que a prevalência de anti-HBcAg na ausência do antígeno de superfície (HBsAg) em indivíduos com hepatite C crônica seja da ordem de 20 a 30% 5,6 . No Brasil, um estudo realizado em Campinas, Estado de São Paulo, envolvendo 790 pré-doadores de sangue nos quais os exames de triagem revelaram anti-VHC(+), demonstrou que 30% dos mesmos apresentavam marcadores de infecção B pregressa 7 .…”
Section: Introductionunclassified